Resource requirements and costs of developing and delivering MOOCs - Fiona M. Hollands (Athabasca University Press, 2014)
Given the ongoing alarm regarding uncontrollable costs of higher education, it would be reasonable to expect not only concern about the impact of MOOCs on educational outcomes, but also systematic efforts to document the resources expended on their development and delivery. However, there is little publicly available information on MOOC costs that is based on rigorous analysis. In this article, we first address what institutional resources are required for the development and delivery of MOOCs, based on interviews conducted with 83 administrators, faculty members, researchers, and other actors in the MOOCspace. Subsequently, we use the ingredients method to present cost analyses of MOOC production and delivery at four institutions. We find costs ranging from $38,980 to $325,330 per MOOC, and costs per completer of $74-$272, substantially lower than costs per completer of regular online courses, by merit of scalability. Based on this metric, MOOCs appear more cost-effective than online courses, but we recommend judging MOOCs by impact on learning and caution that they may only be cost-effective for the most self-motivated learners. By demonstrating the methods of cost analysis as applied to MOOCs, we hope that future assessments of the value of MOOCs will combine both cost information and effectiveness data to yield cost-effectiveness ratios that can be compared with the cost-effectiveness of alternative modes of education delivery. Such information will help decision-makers in higher education make rational decisions regarding the most productive use of limited educational resources, to the benefit of both learners and taxpayers.